Investing in Private Evidence: The Effect of Adversarial Discovery. (16th May 2022) - Guerra, Alice; Parisi, Francesco
Abstract: Much of the conventional wisdom of evidence law rests on the premise that the amount of evidence available in any given case is exogenously determined. With the advent of evidence technology (e.g. dashcams, black-box technology, digital data storage, surveillance cameras), the availability of evidence is substantially controlled by individuals. In this article, we show that evidence rules play an important role in determining individuals' decisions to invest in private evidence. We compare the evidence rules adopted in the USA and Europe and analyze their relative impact on the voluntary adoption of evidence technology. We find that by making private evidence not discoverable, more rather than less evidence would be made available to courts.